2020
DOI: 10.1109/access.2020.3023391
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Differential Game Model Analysis of Emission-Reduction Technology Under Cost-Sharing Contracts in the Carbon Trading Market

Abstract: Climate change and greenhouse gas emission reduction have become pressing concerns in recent years. Carbon trading systems and emission-reduction cost-sharing contracts are important emissionreduction measures, under the two mechanisms, this paper considers a dynamic emission-reduction technology investment decision-making problem in a dyadic supply chain consisting of a manufacturer and a retailer. In considering the influence of consumers' low-carbon preferences on market demand as well as the impact of unce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 21 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…The research results showed that carbon tax can promote LC technology innovation. Hou et al (2020) used the differential game model to explore the dynamic emission reduction technology investment decision-making problem in the binary supply chain composed of manufacturers and retailers. Si et al (2020) established a time-lag differential price game model, and analyzed the equilibrium strategy of price competition between technology supply and demand companies and the local asymptotic stability of the game system at the equilibrium point.…”
Section: Differential Gamementioning
confidence: 99%
“…The research results showed that carbon tax can promote LC technology innovation. Hou et al (2020) used the differential game model to explore the dynamic emission reduction technology investment decision-making problem in the binary supply chain composed of manufacturers and retailers. Si et al (2020) established a time-lag differential price game model, and analyzed the equilibrium strategy of price competition between technology supply and demand companies and the local asymptotic stability of the game system at the equilibrium point.…”
Section: Differential Gamementioning
confidence: 99%
“…Reference [33] contended with the joint emission reduction and pricing decision problems, as well as coordination contract design issue for a class of two-echelon low-carbon supply chain system. The dyadic supply chain system consisting of manufacturer and retailer or production inventory system were discussed, which considered the influence of consumers" low-carbon preferences on random variable demand and the impact of uncertainty on carbon emissionreduction behavior [34]. Through numerical analysis and case study, the validity and feasibility of the viewpoint are verified.…”
Section: B Carbon Emissions Allocation and Abatement Costsmentioning
confidence: 99%
“…The manufacturer M also pays attention to the emission reduction investment of supplier S and the promotion of retailer R. In the meantime, it shares a certain proportion of the costs for the upstream and downstream. The construction method refer to the References [20][21][22], [32][33][34]. Therefore, the decisions of three parties are proposed as.…”
Section: A Non-cooperative Decision-making Strategymentioning
confidence: 99%
“…Many studies have focused on the mitigation potential of CO2 emissions from transport sector [18,19,20,21,22]. Most of these studies are concerned with traditional decoupling analysis of CO2 emissions from the transport sector.…”
Section: Related Workmentioning
confidence: 99%